2022
DOI: 10.1002/admt.202200027
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanowire Synthesis and Applications in Composites: Progress and Prospects

Abstract: Silver nanowires (AgNWs) have gained increased interest as highly conductive and transparent nanomaterials with numerous applications across various fields. Owing to their unique properties (e.g., optical transparency, electrical conductivity, mechanical characteristics, and ease of processing), AgNWs have been extensively investigated for application in light‐emitting diodes, solar cells, electrocatalysis, liquid crystal displays, wearable electronic devices, flexible nanosensors, and supercapacitors. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 183 publications
0
9
0
Order By: Relevance
“…[9][10][11][12][13][14][15] The properties of AgNWs, which lead to their diverse application performance with high optical transparency and low sheet resistance, are significantly determined by their preparation method. 16 Recently, many preparation methods have been reported, including the polyol method, [17][18][19] template method, 20,21 wet chemical method, 22,23 photo-reduction method, 24 and seedmediated method. 25 Previous studies demonstrated that the polyol method is the most promising strategy, but it usually requires high-temperature and high-pressure conditions and its final products need to go through complicated purification, 26 which undoubtedly increases the cost of preparation.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] The properties of AgNWs, which lead to their diverse application performance with high optical transparency and low sheet resistance, are significantly determined by their preparation method. 16 Recently, many preparation methods have been reported, including the polyol method, [17][18][19] template method, 20,21 wet chemical method, 22,23 photo-reduction method, 24 and seedmediated method. 25 Previous studies demonstrated that the polyol method is the most promising strategy, but it usually requires high-temperature and high-pressure conditions and its final products need to go through complicated purification, 26 which undoubtedly increases the cost of preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, silver nanowires (AgNWs), characterized as one-dimensional nanomaterials, offer the advantages of ultrahigh electrical conductivity and thermal conductivity similar to traditional metal materials, along with the high visible light transmittance and lightweight characteristics typical of nanomaterials. 19 Given these aforementioned characteristics, it can be inferred that AgNWs possess considerable potential for application in burgeoning domains, such as the development of materials for EMI shielding.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, over the past few years, scholars have focused on the advancement of composite materials endowed with attributes such as flexibility, lightweight, facile processing, chemical resistance, and enhanced EM-shielding capabilities. Polymer composite EMI shielding materials incorporating conductive nanofillers such as carbon nanotubes, graphene, MXene, and metal nanowires , have gradually attracted the attention of researchers. Among these, silver nanowires (AgNWs), characterized as one-dimensional nanomaterials, offer the advantages of ultrahigh electrical conductivity and thermal conductivity similar to traditional metal materials, along with the high visible light transmittance and lightweight characteristics typical of nanomaterials . Given these aforementioned characteristics, it can be inferred that AgNWs possess considerable potential for application in burgeoning domains, such as the development of materials for EMI shielding.…”
Section: Introductionmentioning
confidence: 99%
“…Among these alternatives, silver generates high interest as it exhibits an electrochemical behavior close to that of ruthenium oxide, is cheaper than ruthenium oxide, and is more environmentally sustainable. , Also, silver in its different oxidation states (AgO, Ag 2 O, and Ag 2 O 2 ) is more conductive than other transition-metal oxides investigated for pseudocapacitor applications and has more ability to change and adopt different oxidation states (+1, +2), providing the energy storage ability. Furthermore, from the electrochemical perspective, silver is very reactive and forms different oxide phases such as AgO, Ag 3 O 4 , Ag 4 O 3 , Ag 2 O 3 , and Ag 2 O, where Ag 2 O is the most stable among them. In addition, silver has been used in previous studies as a component of electrodes; also, silver nanowires are commonly used in flexible and wearable electronic devices. Nanocomposites of silver nanoparticles with graphene, carbon nanotubes, metal oxides, or conducting polymers have been tested for their use in several energy storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, from the electrochemical perspective, silver is very reactive and forms different oxide phases such as AgO, Ag 3 O 4 , Ag 4 O 3 , Ag 2 O 3 , and Ag 2 O, where Ag 2 O is the most stable among them. 17 22 In addition, silver has been used in previous studies as a component of electrodes; also, silver nanowires are commonly used in flexible and wearable electronic devices. Nanocomposites of silver nanoparticles with graphene, carbon nanotubes, metal oxides, or conducting polymers have been tested for their use in several energy storage applications.…”
Section: Introductionmentioning
confidence: 99%